Thoracic Wall Reconstruction with Acellular Porcine Dermal Collagen Matrix - Schmidt, Joachim; Redwan, Bassam; Koesek, Volkan; Heitplatz, Barbara; Bedetti, Benedetta; Aebert, Hermann; Wiebe, Karsten (The Thoracic and Cardiovascular Surgeon, 2016)
Background Major thoracic wall resections require the implantation of foreign materials for reconstruction and stabilization. Recently, biological collagen matrixes have emerged as an alternative to the routinely used synthetic materials.Materials and Methods Retrospectively, we analyzed our initial experience of chest wall reconstruction on large defects using a cross-linked porcine dermal acellular collagen matrix mesh with a thickness of 1.5 mm.Results Six sarcoma patients with a mean age of 46 (22–66) years underwent chest wall resections. Complete thoracic wall defects (mean area 149 cm2) ranged from 8 × 10 to 15 × 20 cm in size. In the majority of cases, only mobilized subcutaneous tissue and skin were used for soft-tissue coverage of the implanted porcine collagen matrix patches. Implantation and postoperative courses were uneventful in all patients. No local infections or wound healing problems occurred. The collagen material resulted in durable and good to excellent chest wall stability in clinical follow-ups, and on computed tomography scans spanning over 3.5 years. Histological examination showed integration, neovascularization, and long-term persistence of the collagen matrix on late reoperation of one patient.Conclusion Acellular porcine dermal collagen matrix is a feasible and reliable biological patch material for reconstruction of the thoracic wall. Excellent wound healing and long-term stability are achieved even in large defects or complete sternal replacements.
Keywords: chest wall; sarcoma; wound healing; sternum; tumor